2015
DOI: 10.1007/s00127-015-1076-4
|View full text |Cite
|
Sign up to set email alerts
|

Greater number of group identifications is associated with lower odds of being depressed: evidence from a Scottish community sample

Abstract: Purpose Group identification has been shown to be associated with reduced risk of depression, but this research has important limitations. Our aim was to establish a robust link between group identification and depression whilst overcoming previous studies' shortcomings. Methods 1824 participants, recruited from General Practice throughout Scotland, completed a questionnaire measuring their identification with three groups (family, community, and a group of their choice), as well as their intensity of contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 31 publications
5
71
2
Order By: Relevance
“…By contrast, there is now a wealth of evidence that multiple group memberships, and the social identities arising from them, are protective in a wide range of contexts, and for both vulnerable and less vulnerable populations (Crabtree, Haslam, Postmes & Haslam, 2010;Gleibs, Haslam, Haslam & Jones, 2011;Khan et al, 2014;Sani et al, 2015, Steffens, Haslam, Schuh, Jetten & van Dick, 2016. Instead, we can infer from the social identity model that there are two reasons why our studies, along with previous research, have found limited evidence for the stress buffering hypothesis -both relating to the measurement of social support.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…By contrast, there is now a wealth of evidence that multiple group memberships, and the social identities arising from them, are protective in a wide range of contexts, and for both vulnerable and less vulnerable populations (Crabtree, Haslam, Postmes & Haslam, 2010;Gleibs, Haslam, Haslam & Jones, 2011;Khan et al, 2014;Sani et al, 2015, Steffens, Haslam, Schuh, Jetten & van Dick, 2016. Instead, we can infer from the social identity model that there are two reasons why our studies, along with previous research, have found limited evidence for the stress buffering hypothesis -both relating to the measurement of social support.…”
Section: Discussioncontrasting
confidence: 79%
“…Social identification has been proposed to be the "active ingredient" in social relationships that provides their protective benefit against depression. Indeed, social identification has been found to be more strongly associated with depression than social contact (Sani, Herrara, Wakefield, Boroch, & Gulyas, 2012;Sani, Madhok, Norbury, Dugard, & Wakefield, 2015). Joining a social group has been found to increase the likelihood of depression recovery and prevent relapse (Cruwys et al, 2013), with studies suggesting that social groups are therapeutic only when they are underpinned by social identification (Cruwys et al, 2014b).…”
Section: A Social Identity Model Of Stressful Life Transitionsmentioning
confidence: 99%
“…First, studies have already revealed a robust link between family identification and mental health. For instance, Sani, Herrera, Wakefield, Boroch, and Gulyas (2012) found a negative association between family identification and depression, satisfaction with life, and perceived stress in a community sample of Polish people, while Sani et al (2015b) recruited a large Scottish community sample and found family identification to contribute to lower odds of being depressed. Furthermore, Naughton, O'Donnell, and Muldoon (2015) found that greater identification with the extended family in young adults was related to a reduction in the detrimental effects of exposure to parental intimate partner violence on anxiety and self-esteem.…”
Section: Aim and Overview Of Researchmentioning
confidence: 99%
“…Group identification is a core human experience which encompasses one's feelings of belonging and connectedness to a social group, coupled with one's sense of sharing standards (values, ideals, goals) with the other members of the group (Sani, Madhok, Norbury, Dugard, & Wakefield, 2015a, 2015b. Importantly, social psychologists taking a social identity perspective on group processes (Haslam, 2004;Tajfel & Turner, 1986;Turner et al, 1987) have found group identification to be consequential for a variety of individual perceptions and behaviors.…”
mentioning
confidence: 99%
“…Because to date researchers have used group identification exclusively as a predictor of psychological well-being outcomes rather than as a psychological well-being outcome itself [15,16,17], we will also assess the alternative possibility that greater identification with both the family group and the group of transplantees will lead to greater PTG over time.…”
Section: Introductionmentioning
confidence: 99%